Incidence of anti-topoisomerase I antibody seroconversion and clinical association in systemic sclerosis - Srikamud, Soraya; Pongkulkiat, Patnarin; Mahakkanukrauh, Ajanee; Suwannaroj, Siraphop; Nanagara, Ratanavadee; Foocharoen, Chingching (Asia-Pacific Journal of Science and Technology, 2021)
Anti-topoisomerase I antibody (ATA) is an autoantibody associating with a poor prognosis in systemic sclerosis (SSc). The changing of ATA from negative to positive or vice versa might have an effect on the outcome. We aimed to define the incidence and to determine the association between clinical parameters and ATA seroconversion. A historical cohort study of adult SSc patients who attended the Scleroderma Clinic, Khon Kaen University, Thailand was conducted. We included all patients tested at least twice for ATA during January 2008-May 2018. ATA positive seroconversion was set when ATA was initially negative but switched to positive over the period of follow-up while ATA negative seroconversion was fulfilled when ATA changed from positive to negative. Forty-eight SSc patients were tested for ATA at least twice. ATA positive seroconversion was not detected during follow up while 2 cases (4.2%) were defined as ATA negative seroconversion with the incidence of 1.0 per 100 person-years (95%CI 0.02-0.4). Both patients presented regression of skin thickness and pulmonary arterial hypertension (PAH). There was no parameter associated with ATA negative seroconversion. There was a low incidence of both ATA negative and positive seroconversion among SSc patients and no significant clinical association by repeating test was detected. Repeating test for ATA may have low clinical utility for SSc patients.